Management and the control of technical labour - Causer, Gordon [Verfasser]; Jones, Carol [Verfasser] (My University, 1996)
"This paper addresses the issues involved in the management of professional employees through an examination of the managment of professional engineers in a sample of electronic companies. It is argued that a measure of evaluation and control is secured through the development of organisational position which combine elements of both technical and managerial work and through the operation of personalised systems of reward. the potentially demotivating effects of hierarchical structures of control are moderated by forms of work organisation which blur the distinction between employees and management, and by the development of managerial philosophies which stress a commonality of identity uniting those at different levels of the organisational hierarchy. The development of such philosophies is related to the nature of professional organisation within engineering and to the male-dominated nature of the work environment. the paper concludes with a brief consideration of the qpplicability of this analysis to the study of the management of professional employees more generally." (author's abstract, IAB- Doku) ((en)) Der Beitrag befasst sich mit der Leistungsbewertung von hochqualifizierten Experten am Beispiel von britischen Ingenieuren, die in Unternehmen der Elektrotechnik beschäftigt sind. Es wird aufgezeigt, dass organisatorische Positionen, die Fach- und Führungstätigkeiten kombinieren, eine Bewertung und Kontrolle von Technikexperten möglich macht. (IAB)
Keywords: S 6.3.1 Ingenieurberufe, Chemiker, Physiker, Mathematiker; S 2.2.4 Anrechnung, Prüfung & Zertifizierung; G 1.2.4.1.4 Verarbeitendes Gewerbe; P 1.3 Frauen; I 2.2.1 Westeuropa; Ingenieur; Experte; Führungskraft; Hochqualifizierter; Leistungsbewertung; Elektrotechnische Industrie; Berufsproblem; Frauen in Einzelberufen; Frauenarbeit; Großbritannien